Giardiasis in daycare centers at Rancabali tea plantation, Bandung District, Indonesia - Endang Widajanti; Herry Garna; Alex Chairulfatah; Dadang Hudaya (Indonesian Pediatric Society, 2003)
Background In developing countries, the prevalence of giardia-sis in daycare centers is considerably high. There had been inad-equate report of giardiasis in Indonesia.Objective To know the prevalence of giardiasis in children andthe number of children with symptomatic and asymptomatic giar-diasis who attended daycare centers at Rancabali tea plantation,Bandung district.Methods This descriptive study was conducted in daycare cen-ters between August to October 2002. Giardiasis was defined asthe occurrence of G. lamblia cyst in stool specimen independentfrom the presence or absence of symptoms. Four of 12 daycarecenters were chosen by cluster random sampling. All children aged1 to 60 months attending daycare and staying for at least 2 weekswere included in this study. Three consecutive stool specimen pre-served by 10% formalin, concentrated by formalin ether, were ex-amined microscopically to find the G. lamblia cyst.Results Giardia lamblia cysts were found in 27 (29%) of the 92children attending the daycare centers at Rancabali tea plantation(95%CI 20;38.6%). Of these children, 15 showed symptoms suchas diarrhea episodes (8 children), diarrhea (5 children), bloating (5children), abdominal cramp (5 children), and vomiting (3 children).Three children showed mild to moderate malnutrition. Ten childrenaged 13 to 36 month-old with G. lamblia-positive stool showed suchsymptoms.Conclusion The prevalence of G. lamblia infection in children at-tending daycare centers at Rancabali tea plantation was almostsimilar with other place in developing countries. More than half ofpatients had symptomatic disease